A Cinchona Alkaloid‐Functionalized Mesostructured Silica for Construction of Enriched Chiral β‐Trifluoromethyl‐β‐Hydroxy Ketones over An Epoxidation‐Relay Reduction Process. Issue 14 (28th June 2016) - Li, Cuibao; Shu, Xiaomin; Li, Liang; Zhang, Genwei; Jin, Ronghua; Cheng, Tanyu; Liu, Guohua
Abstract: A cinchona alkaloid‐functionalized heterogeneous catalyst is prepared through a thiol‐ene click reaction of chiral N ‐(3, 5‐ditrifluoromethylbenzyl)quininium bromide and a mesostructured silica, which is obtained by co‐condensation of 1, 2‐bis(triethoxysilyl)ethane and 3‐(triethoxysilyl)propane‐1‐thiol. Structural analyses and characterizations disclose its well‐defined chiral single‐site active center, and electron microscopy images reveal its monodisperse property. As a heterogenous catalyst, it enables an efficient asymmetric epoxidation of achiral β‐trifluoromethyl‐β, β‐disubstituted enones, the obtained chiral products can then be converted easily into enriched chiral β‐trifluoromethyl‐β‐hydroxy ketones through a sequential epoxidation‐relay reduction process. Furthermore, such a heterogeneous catalyst can be recovered conveniently and reused in asymmetric epoxidation of 4, 4, 4‐trifluoro‐1, 3‐diphenylbut‐2‐enone, showing an attractive feature in a practical construction of enriched chiral β‐CF3 ‐substituted molecules. Abstract : A cinchona alkaloid‐functionalized mesostructured silica enables an efficient asymmetric epoxidation of achiral β‐trifluoromethyl‐β, β‐disubstituted enones, the obtained chiral products can then be coverted to enriched chiral β‐trifluoromethyl‐β‐hydroxy ketones through a sequential epoxidation‐relay reduction process (see scheme). The superior catalytic performance is attributed to the hydrophobic mesoporous organosilica network, uniformly distributed active species, and confined cinchona alkaloid catalytic nature.